2022
DOI: 10.1097/fjc.0000000000001386
|View full text |Cite
|
Sign up to set email alerts
|

The Significance of Statin Associated Muscle Symptoms and Its Impact on Patients Adherence and Outcomes

Abstract: Statin-associated muscle symptoms (SAMS) are one of the most common side effects of statins. This study aimed to explore the significance of SAMS among statin users by comparing statin users with a control group. To achieve our aims, a propensity score matching the retrospective cohort study was conducted in a single center tertiary hospital. The statin muscle symptoms were assessed using the Proposed Statin Myalgia Index Score, whereas the patient's adherence to medications was evaluated using the Morisky Med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…However, statin-associated muscle symptoms (SAMS) are still one of the most prevalent statin adverse events, especially in those on moderate- or high-intensity therapy. Furthermore, individuals who have autoimmune diseases and those who are on antiepileptic medications were found to have significantly higher rates of SAMS [ 84 ]. Therefore, healthcare providers must be aware of these adverse events and address them appropriately to ascertain the adherence of patients to their prescribed medications, thus reducing cardiovascular events.…”
Section: Resultsmentioning
confidence: 99%
“…However, statin-associated muscle symptoms (SAMS) are still one of the most prevalent statin adverse events, especially in those on moderate- or high-intensity therapy. Furthermore, individuals who have autoimmune diseases and those who are on antiepileptic medications were found to have significantly higher rates of SAMS [ 84 ]. Therefore, healthcare providers must be aware of these adverse events and address them appropriately to ascertain the adherence of patients to their prescribed medications, thus reducing cardiovascular events.…”
Section: Resultsmentioning
confidence: 99%
“…6 However, further studies are needed to better clarify the association between risk factors and SAMS. In fact, Al-Makhamreh et al, 7 in their observational retrospective cohort study, did not confirm gender, and both kidney and hepatic impairment association with an increased risk of SAMS onset, giving more prominence instead to the presence of autoimmune diseases. Moreover, a recent metanalysis pointed out that statin therapy causes approximately 11 additional reports of any muscle pain or weakness per 1000 patients during the first year, with only a little increase thereafter, with some evidence of persistent risk for more intensive regimens.…”
mentioning
confidence: 85%
“…Of these, some patients complained that they were not properly informed about side effects before starting statin treatment. 8 Al-Makhamreh et al, 7 in their recent article, have reported a non–statistically significant difference between patients experiencing SAMS and the control group. This finding might be due to the improvement in doctor–patient relationship, to patient involvement in assessing and managing adverse effects, which rarely represent a life-threatening condition (myopathy incidence is ∼1 in 10,000 per year; rhabdomyolysis incidence ∼1 in 100,000 per year), and to the increase in patient knowledge about the risk–benefit ratio of statin therapy use and discontinuation.…”
mentioning
confidence: 94%
See 2 more Smart Citations